Lived experiences of Korean students in socials networking sites engagement: towards developing English language proficiency - Lee, Seung Lee (Parañaque City: Olivarez College, 2014)
The primary aim of this study was to explore and describe the lived experiences of EFL learners engaged in social networking sites, specifically, Facebook using, existential phenomenology find answers to the following central question and sub-questions: Central Question: What is the essence of the lived experiences of EFL learners engaged in social network sites? Corollary Questions: You sent 1. What are EFL learner's engagements in social network sites? 2. Which factors affect their motivation and engagement? 3. What should facilitator do to encourage/promote the engagement? 4. Based on the findings of the study, what SNS for SLA Guidebook maybe proposed?
Master Thesis